2021
DOI: 10.1177/17474930211048323
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke fatigue is associated with resting state posterior hypoactivity and prefrontal hyperactivity

Abstract: Tumor detection supported by Raman spectroscopy is becoming increasingly popular, yet the relevance of spectral variation and feature selection retains unclear. Here we determined the correlation and difference between spectral characteristic and feature evaluation for leukocytes and tumor cells. Some peaks were found to show noticeable spectral differences, and their intensity distributions were investigated, finding using Log-Normal distribution to describe Raman intensity pattern may be more appropriate. Fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…A recent fMRI study indicated that PSF was associated with the posterior hypoactivity and prefrontal hyperactivity reflecting that dysfunction within fronto-striatal-thalamic and frontal-occipital networks may be involved in the occurrence of fatigue, which was partially consistent with our findings (Cotter et al, 2021 ). In addition, the prevalence of PSF in this study was 39.8% in the acute phase of stroke and 35.8% at the 6-month follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…A recent fMRI study indicated that PSF was associated with the posterior hypoactivity and prefrontal hyperactivity reflecting that dysfunction within fronto-striatal-thalamic and frontal-occipital networks may be involved in the occurrence of fatigue, which was partially consistent with our findings (Cotter et al, 2021 ). In addition, the prevalence of PSF in this study was 39.8% in the acute phase of stroke and 35.8% at the 6-month follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Both in post-stroke and MS fatigue, there are several reports of altered resting state connectivity 14,5458 . In stroke, suggestions of parietal hypoconnectivity and frontal hyper connectivity 58 with reversed inter-hemispheric balance of connectivity 14 , are implicated in manifestation of fatigue. In MS, changes in default mode network 56 and involvement of striatal circuits involved in movement, sensation and motivation 55 have all been implicated in development of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Both in post-stroke and MS fatigue, there are several reports of altered resting state connectivity 14,[54][55][56][57][58] . In stroke, suggestions of parietal hypoconnectivity and frontal hyper connectivity 58 with reversed inter-hemispheric balance of connectivity 14 , are implicated in manifestation of fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies with 2755 participants tested the association between fatigue and lesion diameter or volume. 1,7,20,21,31,32,35,43,[44][45][46][47][48][49]52,53 None identified any significant associations (see Supplementary sTable 4).…”
Section: Lesion Volumementioning
confidence: 99%